A Reação de Diels - Alder de p-benzoquinonas sob efeito de microondas - Donatoni, Maria Carolina (Universidade Federal de São Carlos, 2008)
In this work it was done a study of the microwave effect on Diels - Alder reaction of the p-benzoquinones thymoquinone (A1), 2,5-dimethyl-p-benzoquinone (A2) and 2,6-dimethyl-pbenzoquinone (A3) with the dienes cyclopentadiene (BB1), 2,3-dimethyl-1,3- butadiene (B2B ), isoprene (BB3) and trans-pyperilene (B4B ) (Figure Ι). These reactions were also held under conventional thermal conditions and catalysis with the Lewis acid SnCl4 in order to make a comparison of the results. It was also studied the Diels - Alder reaction in multicomponent version between thymoquinone (A1), trans-2-pentenal and acetamide under microwave effect (Figure ΙΙ). (FORMULA)Regarding the Diels - Alder reaction between p-benzoquinones (A1 - A3) and dienes (BB1 - B4B ) it was observed a reduction of the reaction time, obtaining higher yields and less formation of by - products, all in comparison with the results of the same reactions performed under thermal conventional condition and catalytic condition with SnCl4. This work also involved the study of the microwave effect on Diels - Alder reaction between cyclopentadiene (BB1) and mono-oximes dienophiles C1, C2 and C3 (Figure ΙΙΙ). These reactions had already been carried out in our laboratory, but under conventional thermal and catalytic conditions (Lewis acids). Under such conditions, the mono-oxime starting material was recovered, or a complex mixture of polymerization products was formed. (FORMULA)The reactions of compounds C1, C2 and C3 with cyclopentadiene (BB1) under microwave effect showed similar results with those that were obtained when these reactions were carried out under conventional thermal and catalytic conditions, thus leading to recovery of the mono-oxime starting material or a complex mixture of products which could not be identified.
The diels-alder reaction of p-benzoquinones under microwave effect
Keywords: Diels-Alder; Microondas; Para-Benzoquinonas; CIENCIAS EXATAS E DA TERRA::QUIMICA